Neighborhood Collective Efficacy Moderates the Association between Maternal Adverse Childhood Experiences and Marital Conflict. Issue 3 (2nd June 2016) - Madigan, Sheri; Wade, Mark; Plamondon, André; Jenkins, Jennifer M.
Abstract: In a socio‐demographically diverse sample of 501 caregivers participating in a longitudinal birth cohort study during the childbearing years, we examined whether neighborhood collective efficacy moderated the association between maternal adverse childhood experience (ACEs) and marital conflict. Maternal ACEs were assessed via retrospective reports. Neighborhood collective efficacy was measured via maternal and paternal reports at 2 months, and maternal reports of marital conflict were collected at infant age 2 and 18 months. Multiple linear regression analyses revealed that maternal ACEs were associated with increased marital conflict. Neighborhood collective efficacy moderated the association between early maternal ACEs and marital conflict, such that mothers experiencing ACEs had lower levels of marital conflict when exposed to high levels of neighborhood collective efficacy. Results suggest that extra‐familial sources of social support and control, such as feelings of security, trust, order, and connectedness with others, may buffer the effects of early adversity on marital discord.